A DISCOURSE ANALYSIS OF "YOUR LETTERS" IN THE JAKARTA POST NEWSPAPER - PURNASARI , SRI HANDAYANI (2007)
This study aims at describing the elements which build the discourse of 'Your Letters' in the Jakarta Post Newspaper and identifying deixis devices in 'Your Letters' in the Jakarta Post Newspaper. This research is descriptive qualitative research in which the analysis uses the elements of making the letters commonly called the parts of letter. The researcher collects the data by using the observation method. The result shows that: (1) the most configurations that the researcher found in those letters are: (a) subject line which is written in the bold font in the first line of the letter and has function to make easy for the readers to understand the content of the letter, (b) body of letter which is the main part of the lay out and has three main parts; introduction, purposes and conclusion, (c) the sender is written in the bottom right of the letter and consists of the writer's name and the place of the letter written, but there is one letter the has different type of the sender. The subject of these letter is 'USAID Clarifies'. In this letter, the sender is consist of the sender's name and the profession; (2) the most deixis that be used in discourse "Your Letters" in the Jakarta Post Newspaper are: (a) personal deixis is the use of reference which moves or changes depend on participant role, (b) place deixis is the use of adverb of place as the location of the speech, (c) time deixis is the use of adverb od time as the time of speech, (d) discourse deixis has to do with encoding of reference that includes the text referring expression is located.